Nepal, India, and China: the Two plus One Discourse - Timalsina, Saroj Kumar (The Batuk, 2022)
China, India, and Nepal all have distinct and long-standing bilateral relationships. The time has now come to foster tripartite ties and enhance cooperation through joint efforts for shared benefits. In this regard China has proposed a ‘two plus one’ cooperation model between China, India and Nepal. This study has been conducted to depict the impact of the model to the relations between three countries. Using the desk work method for obtaining data and descriptive as well as the analytical method for interpreting the information, the study found that Nepal suspects that the role of China and India will be bigger than Nepal and thus strongly opposes the proposal. On the other hand, though China defines that the concept promotes the trilateral relations between the nations, India is uninterested on it. India does not want to lose its big brotherly grip over Nepal and let China enhance the presence in Nepal. This study concluded that the trilateral cooperation model is the only way that Nepal should foster to balance the role of two giant neighbors.